2022
DOI: 10.1177/20503121211066682
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related anxiety and knowledge toward its preventive measures among patients with chronic medical illness on follow-up in public hospitals of Bale, East Bale, and West Arsi zones, Ethiopia

Abstract: Background: Coronavirus disease 2019, also known as 2019-nCoV cluster of acute respiratory illness with unknown causes, which occurred in Wuhan, Hubei Province, in China, was first reported to World Health Organization country office as of December 30, 2019. People with medical illness are at a higher risk for coronavirus disease, and the pandemic influences mental health and causes psychological problems, particularly in those with chronic medical illness. Hence, this study aimed to assess coronavirus disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 79%
“…Among this, 14 studies focused on chronic disease patients, five focused on diabetes, three focused on hypertension, two focused on diseases and/ or hypertension, one focused on cancer, and one focused on cardiovascular disease. The review findings were organized into five frequently reported themes and subthemes: these are 1) disruption of follow-up care and poor health care utilization reported by 11 studies [10,11, 23,24,25,26,27,28,29,30,31]; 2) increased anxiety, stress, depression, and increased mental health problems reported by eight studies [15,32, 34,35,37,38,39,43]; 3) substance use reported by four studies [36,37,41,44]; 4) decreased physical activity and sedentary life reported by three studies [33,36,44]; and 5) increased food insecurity and poor dietary habits due to COVID-19 among NCDs patients, reported in five studies [36,40,42,43,44] Studies included in this review did not focus on the same subject matter. Some studies focused on one theme and others focus on more than two themes; for instance, (Andualem et al, 2020) examined adherence to lifestyle modifications and reported on diet, exercise, smoking, and alcohol, whereas (Abate et al, 2022) examined adherence to physical exercise recommendations and reported only on exercise compliance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this phase, a comprehensive review of the full-text articles was conducted, excluding 186 studies from further consideration. A total of 23 studies, including 21 studies for knowledge, 10,12,13,15,[17][18][19][20][21][22][23][26][27][28][29][30][31][32][33][34][35] 12 studies for attitudes, 10,12,14,15,[19][20][21]23,29,30,34,35 and 12 studies for practice 10,12,[18][19][20][21]23,[29][30][31]35 were included in the meta-analysis (Figure 1).…”
Section: Eligibility Studies and Search Resultsmentioning
confidence: 99%
“…Yapılan çalışmalar sonucunda, Covid-19 salgını kronik hastalıklara sahip bireylerde anksiyete artışına neden olmuştur. [24][25][26][27][28] 37 çalışmanın incelendiği bir meta analiz çalışmasında pandemi döneminde bireylerin Covid-19 ile ilişkili anksiyete seviyelerinde önemli derecede artış olduğu belirlenmiştir. 29 Yine Türkiye'de Çıtak ve Pakdemir (2020)' in pandemi döneminde yaptıkları çalışmada araştırmaya katılan katılımcıların büyük oranda (%40) kaygı seviyelerinin normal sınırların üzerinde olduğu belirlenmiştir.…”
Section: Verilerin Değerlendirilmesiunclassified